Phase evolution and microstructure analysis of Al2O3–ZrO2(Y2O3) eutectic powders with ultra-fine nanostructure. Issue 17 (1st December 2019) - Yu, Wanjun; Zheng, Yongting; Pan, Jiayu; Yu, Yongdong
Abstract: It is difficult to prepare high-quality eutectic particles with regular morphologies and fine microstructure by current technologies. In this work, the Al2 O3 –ZrO2 (Y2 O3 ) eutectic powders with ultra-fine nanostructure is fabricated by a novel combustion synthesis combined with spray cooling (CS-SC) method. The phase structure and microstructure of eutectic particles with different Y2 O3 content are discussed in details. The doping of Y2 O3 inhibits the transformation of cubic-tetragonal and tetragonal-monoclinic during the solidification process, which gives rise to a rich variety of ZrO2 polymorphs. Moreover, the microstructure of eutectic particles papered by CS-SC is independent of Y2 O3 content, which are predominantly manipulated by cooling rate. The evolution of eutectic structure with particle size is also detailly analyzed. The cooling rate declines with the of particle size, which leads to increase of growth rate and consequently resulting in coarse structure. But all for this, the mean phase spacings of all particles remain nanoscale. The CS-SC has much higher growth rate and degree of supercooling than other solidification techniques. This work provides a basis for preparing Al2 O3 –ZrO2 (Y2 O3 ) eutectic ceramics concurrent with large dimension and ultra-fine structure via sintering method.